METODE RESITASI (PENUGASAN) DALAM MENINGKATKAN MOTIVASI BELAJAR BIMBINGAN DAN KONSELING DI MAN 2 BANYUWANGI - Jon Iskandar Bahari (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2019)
Problems occurred in the process of teaching and learning classes include students ' lack of interest in material with guidance and counselling, is evident when students are given assignments, students are always asking for the value of the results of that task. Students are also less interested in guidance and counselling to the materials due to subjects guidance and counselling is not included in the assessment of students ' report cards like other subjects. Students also concede rarely read books module that had belonged to him. Also teaching methods that have been applied to teachers BK less attractive and varied, this can be shown when the teacher would do with multimedia learning methods many tools that are not available by the school and can be known that with apply method resitasi can improve the learning motivation of students in this class, because by giving many variations in giving the task of making students do not get tired, especially when the implementation of the tasks carried out were not monotonous in the classes only. From the suggestions and criticisms from students to teachers can praktikan known that the students love it when given a task that many model variations and interesting.